Functional neuropathology of neonatal hypoxia‐ischemia by single‐mouse longitudinal electroencephalography. Issue 12 (12th October 2022) - Johnson, Kevin J.; Moy, Brianna; Rensing, Nicholas; Robinson, Alexia; Ly, Michael; Chengalvala, Ramya; Wong, Michael; Galindo, Rafael
Abstract: Objective: Neonatal cerebral hypoxia‐ischemia (HI) results in symptomatic seizures and long‐term neurodevelopmental disability. The Rice‐Vannucci model of rodent neonatal HI has been used extensively to examine and translate the functional consequences of acute and chronic HI‐induced encephalopathy. Yet, longitudinal electrophysiological characterization of this brain injury model has been limited by the size of the neonatal mouse's head and postnatal maternal dependency. We overcome this challenge by employing a novel method of longitudinal single‐mouse electroencephalography (EEG) using chronically implanted subcranial electrodes in the term‐equivalent mouse pup. We characterize the neurophysiological disturbances occurring during awake and sleep states in the acute and chronic phases following newborn brain injury. Methods: C57BL/6 mice underwent long‐term bilateral subcranial EEG and electromyographic electrode placement at postnatal day 9 followed by unilateral carotid cauterization and exposure to 40 minutes of hypoxia the following day. EEG recordings were obtained prior, during, and intermittently after the HI procedure from postnatal day 10 to weaning age. Quantitative EEG and fast Fourier transform analysis were used to evaluate seizures, cortical cerebral dysfunction, and disturbances in vigilance states. Results: We observed neonatal HI‐provoked electrographic focal and bilateral seizures during or immediately following global hypoxia and most commonly contralateral to the ischemic injury. Spontaneous chronic seizures were not seen. Injured mice developed long‐term asymmetric EEG background attenuation in all frequencies and most prominently during non–rapid eye movement (NREM) sleep. HI mice also showed transient impairments in vigilance state duration and transitions during the first 2 days following injury. Significance: The functional burden of mouse neonatal HI recorded by EEG resembles closely that of the injured human newborn. The use of single‐mouse longitudinal EEG in this immature model can advance our understanding of the developmental and pathophysiological mechanisms of neonatal cerebral injury and help translate novel therapeutic strategies against this devastating condition.